Carbon-based perovskite solar cell and preparation method thereof

By adopting stacked structure and in-situ pressure annealing treatment in carbon-based perovskite solar cells, the problem of poor interface contact between the carbon electrode layer and the perovskite active layer is solved, and the photoelectric conversion efficiency and stability are improved effect.

CN119497549AActive Publication Date: 2025-02-21CHINA NAT PETROLEUM CORP +1

Patent Information

Application Number
CN202311022169.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-21
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

In existing carbon-based perovskite solar cells, the interface contact between the carbon electrode layer and the perovskite active layer is poor, resulting in obvious hysteresis effect and low photoelectric conversion efficiency.

Method used

The preparation method of laminated structure is adopted, including a transparent conductive substrate, an electron transport layer, a mesoporous layer, a perovskite active layer and a carbon electrode layer, and the perovskite active layer is subjected to secondary crystallization by in-situ pressure annealing treatment. , reduce the density of defect states and improve interface contact.

Benefits of technology

It improves the binding force and interface contact between the perovskite active layer and the carbon electrode layer, enhances the transmission of hole carriers, improves the photoelectric conversion efficiency of carbon-based perovskite solar cells, and reduces the hysteresis effect. At the same time, the stability of the device is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497549A_ABST
    Figure CN119497549A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-based perovskite solar cell and a preparation method thereof. The method comprises a step of preparing a laminated structure, the laminated structure comprises a transparent conductive substrate, and an electron transport layer, a mesoporous layer, a perovskite active layer and a carbon electrode layer which are sequentially laminated on the surface of the transparent conductive substrate, and the carbon electrode layer comprises a main body layer part and an electrode part. The main body layer part is arranged on the surface of the side, away from the transparent conductive substrate, of the perovskite active layer, the electrode part is arranged on the transparent conductive substrate and makes contact with the electron transport layer, the mesoporous layer and the perovskite active layer, and the surface of the side, away from the transparent conductive substrate, of the electrode part is flush with the surface of the side, away from the transparent conductive substrate, of the main body layer part. After the step of preparing the laminated structure, the preparation method comprises the following steps: applying a pressure perpendicular to the laminated structure to the laminated structure and simultaneously carrying out annealing treatment to obtain the carbon-based perovskite solar cell. By adopting the method provided by the invention, the stability of the carbon-based perovskite solar cell can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor devices, and in particular to a carbon-based perovskite solar cell and a preparation method thereof. Background Art

[0002] Photovoltaic technology is increasingly playing a role in the new energy system. Currently, perovskite solar cells are one of the research hotspots in the photovoltaic field. Since its introduction, it has achieved a certified photoelectric conversion efficiency of 26%, and is expected to enter the photovoltaic market. However, expensive hole transport materials and metal electrodes, as well as complex and energy-intensive vacuum evaporation processes, have significantly increased the cost of perovskite solar cells.

[0003] Carbon materials are inexpensive, abundant in reserves, chemically stable, and easy to modify on the surface. As electrode materials, they also have certain hole transport capabilities. Therefore, carbon-based perovskite solar cells without a hole transport layer have received widespread attention in recent years. Carbon-based perovskite solar cells without a hole transport layer are generally composed of transparent conductive glass, an electron transport layer, a perovskite light-absorbing layer, and a carbon electrode, in which the carbon electrode is both a counter electrode and plays a role in transporting hole carriers. Compared with traditional structural devices, carbon-based perovskite solar cells without a hole transport layer lack a hole transport layer, and the carbon electrode prepared by the scraping method has poor contact with the perovskite layer, resulting in a short transmission distance of hole carriers between the perovskite layer and the carbon electrode interface, severe carrier recombination, and low photoelectric conversion efficiency of the device.

[0004] In order to improve the contact between the carbon electrode and the perovskite layer, enhance the transmission of hole carriers between the carbon electrode and the perovskite layer, and optimize the device performance, chemical strategies such as additives, passivation engineering, and inserting intermediate layers are usually used. However, the process of preparing the carbon electrode requires a certain amount of heating, which can cause the additive to react with the perovskite layer or the additive to become ineffective after heating, which is not conducive to device performance.

[0005] Therefore, it is urgent to develop a preparation method for carbon-based perovskite solar cells to improve the contact between the carbon electrode and the perovskite active layer, optimize the transmission of carriers at the interface, achieve efficient carrier separation, and improve the photoelectric conversion efficiency of carbon-based perovskite solar cells without hole transport layers. Summary of the invention

[0006] The main purpose of the present invention is to provide a carbon-based perovskite solar cell and a preparation method thereof, so as to solve the problem in the prior art that the interface contact between the carbon electrode layer and the perovskite active layer in the carbon-based perovskite solar cell is poor, resulting in obvious hysteresis effect and low photoelectric conversion efficiency.

[0007] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a carbon-based perovskite solar cell, including the step of preparing a laminated structure, the laminated structure including a transparent conductive substrate and an electron transport layer, a mesoporous layer, a perovskite active layer and a carbon electrode layer sequentially stacked on its surface. After the step of preparing the laminated structure, the preparation method includes: applying a pressure perpendicular to the laminated structure to the laminated structure and simultaneously performing annealing treatment to obtain a carbon-based perovskite solar cell.

[0008] Furthermore, a Hoffman clamp is used to apply pressure to the laminate structure; and / or, the annealing treatment includes a heating stage, a heat preservation stage and a cooling stage; preferably, the pressure is 10 to 100 Pa, the heating rate in the heating stage is 6 to 10°C / min, the temperature in the heat preservation stage is 40 to 65°C, and the heat preservation time is 2 to 12 min.

[0009] Furthermore, the carbon electrode layer is prepared by a scraping method; preferably, the thickness of the carbon electrode layer is 5 to 20 μm.

[0010] Furthermore, the perovskite active layer is prepared by a two-step anti-solvent method and a spin coating method; preferably, the thickness of the perovskite active layer is 400 to 560 nm; and / or, the material of the perovskite active layer is Cs 1-x FA x PbI3, where FA is formamidine, 0.77≤x≤0.82.

[0011] Furthermore, when the material of the perovskite active layer is Cs 0.21 FA 0.79 When the material of the perovskite active layer is Cs, the pressure is 55-60 Pa, the heating rate in the heating stage is 8-10 ° C / min, the temperature in the insulation stage is 58-62 ° C, and the insulation time is 8-12 min. 0.23 FA 0.77 When the material of the perovskite active layer is Cs, the pressure is 20-55 Pa, the heating rate in the heating stage is 6-9 °C / min, the temperature in the insulation stage is 40-50 °C, and the insulation time is 4-8 min. 0.19 FA 0.81 When PbI3 is used, the pressure is 65-100 Pa, the heating rate in the heating stage is 7-9°C / min, the temperature in the insulation stage is 46-60°C, and the insulation time is 2-5 min.

[0012] Furthermore, when the thickness of the carbon electrode layer is 5 to 10 μm, the pressure is 50 to 75 Pa, the heating rate in the heating stage is 6 to 7°C / min, the temperature in the insulation stage is 54 to 62°C, and the insulation time is 8 to 12 min; when the thickness of the carbon electrode layer is 13 to 20 μm, the pressure is 30 to 58 Pa, the heating rate in the heating stage is 6 to 9°C / min, the temperature in the insulation stage is 47 to 60°C, and the insulation time is 7 to 11 min.

[0013] Furthermore, the electron transport layer is prepared by chemical bath deposition, spin coating or magnetron sputtering; preferably, the thickness of the electron transport layer is 20 to 60 nm; and / or, the material of the electron transport layer is selected from one or more of the group consisting of titanium dioxide, tin dioxide and zinc oxide.

[0014] Furthermore, the mesoporous layer is prepared by spin coating; preferably, the thickness of the mesoporous layer is 50-94 nm; and / or, the material of the mesoporous layer is selected from one or more of the group consisting of titanium dioxide, aluminum oxide and zirconium oxide.

[0015] Furthermore, the transparent conductive substrate is selected from one or more of the group consisting of FTO conductive glass, ITO conductive glass and IZO conductive glass.

[0016] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a carbon-based perovskite solar cell, which is prepared by the preparation method of the above-mentioned carbon-based perovskite solar cell provided in the present application.

[0017] By applying the technical solution of the present invention, the stacked structure is subjected to in-situ pressure annealing, so that the perovskite active layer can be subjected to secondary crystallization, thereby reducing the defect state density of the perovskite active layer, effectively reducing the stress inside the perovskite active layer itself and between it and the carbon electrode layer in the carbon-based perovskite solar cell, and improving the binding force between the perovskite active layer and the carbon electrode layer, and improving the interface contact between the two, thereby improving the extraction and transmission of hole carriers between the perovskite active layer and the carbon electrode layer, improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and reducing the hysteresis effect. Moreover, the improvement of the interface contact between the perovskite active layer and the carbon electrode layer in the carbon-based perovskite solar cell can effectively inhibit the infiltration of external moisture, thereby improving the stability of the carbon-based perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0019] Figure 1A schematic structural diagram of a carbon-based perovskite solar cell in a preferred embodiment of the present application is shown;

[0020] Figure 2 The current-voltage curve diagram (JV curve diagram, forward scan) of the carbon-based perovskite solar cell prepared in Example 1 and Comparative Example 1 of the present application is shown;

[0021] Figure 3 The current-voltage curve (JV curve, reverse scan) of the carbon-based perovskite solar cell prepared in Example 1 and Comparative Example 1 of the present application is shown.

[0022] The above drawings include the following reference numerals:

[0023] 10. Transparent conductive substrate; 20. Electron transport layer; 30. Mesoporous layer; 40. Perovskite active layer; 50. Carbon electrode layer. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0025] As described in the background technology, the existing carbon-based perovskite solar cells have poor interface contact between the carbon electrode and the perovskite active layer, resulting in obvious hysteresis effect and low photoelectric conversion efficiency. In order to solve the above technical problems, the present application provides a method for preparing a carbon-based perovskite solar cell, including the step of preparing a laminated structure, the laminated structure includes a transparent conductive substrate 10 and an electron transport layer 20, a mesoporous layer 30, a perovskite active layer 40 and a carbon electrode layer 50 stacked on its surface in sequence, the carbon electrode layer 50 includes a main layer part and an electrode part, the main layer part is arranged on the side surface of the perovskite active layer 40 away from the transparent conductive substrate 10, the electrode part is arranged on the transparent conductive substrate 10, and is arranged in contact with the electron transport layer 20, the mesoporous layer 30, and the perovskite active layer 40, and the electrode part and the main layer part are flush with the side surface away from the transparent conductive substrate 10, after the step of preparing the laminated structure, the preparation method includes: applying a pressure perpendicular to the laminated structure to the laminated structure while performing an annealing treatment to obtain a carbon-based perovskite solar cell.

[0026] The most commonly used post-processing methods for perovskite solar cells currently use chemical methods that introduce additives. Considering that the preparation of carbon-based perovskite solar cells requires high-temperature heating for the preparation of carbon electrodes, the added chemical reagents may thermally decompose or react with the perovskite during the heating process, resulting in reduced performance of the perovskite solar cell.

[0027] This application is passed by Figure 1The stacked structure shown is subjected to in-situ pressure annealing, which can cause the perovskite active layer 40 to undergo secondary crystallization, thereby reducing the defect state density of the perovskite active layer 40, effectively reducing the stress inside the perovskite active layer 40 itself and between it and the carbon electrode layer 50 in the carbon-based perovskite solar cell, improving the binding force between the perovskite active layer 40 and the carbon electrode layer 50, improving the interface contact between the two, improving the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and reducing the hysteresis effect. Moreover, the improvement of the interface contact between the perovskite active layer 40 and the carbon electrode layer 50 in the carbon-based perovskite solar cell can effectively inhibit the infiltration of external moisture, thereby improving the stability of the carbon-based perovskite solar cell.

[0028] In a preferred embodiment, a Hoffman clamp is used to apply pressure to the laminated structure. Compared with other pressurizing devices, the use of a Hoffman clamp to apply pressure to the laminated structure is conducive to more accurate control of the magnitude of the pressure, which is conducive to easier regulation of the physical contact between the perovskite active layer 40 and the carbon electrode layer 50, thereby facilitating the improvement of the photoelectric conversion efficiency of the carbon-based perovskite solar cell and reducing the hysteresis effect. In addition, the operation of the Hoffman clamp is simple and economical, and no expensive high-end processing equipment is required, which is conducive to reducing the preparation cost.

[0029] It should be noted that the material of the Hoffman clamp used in the present application can be a metal alloy, and there is no special requirement for the size, as long as it can accommodate the above-mentioned laminated structure provided in the present application.

[0030] In a preferred embodiment, the annealing process includes a heating stage, a heat preservation stage and a cooling stage.

[0031] In a preferred embodiment, the pressure is 10-100 Pa, the heating rate in the heating stage is 6-10°C / min, the temperature in the insulation stage is 40-65°C, and the insulation time is 2-12 min. The applied pressure, the heating rate in the heating stage, the temperature and insulation time in the insulation stage include but are not limited to the above ranges. Limiting them within the above ranges is beneficial to improving the binding force between the perovskite active layer 40 and the carbon electrode layer 50, and is beneficial to improving the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, thereby improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and at the same time helping to reduce the hysteresis effect.

[0032] In a preferred embodiment, the carbon electrode layer 50 is prepared by a scraping method. Compared with other methods, the scraping method is beneficial to improve the uniformity of the properties of the carbon electrode layer 50, thereby improving the electrochemical performance of the carbon-based perovskite solar cell and reducing the preparation cost.

[0033] In a preferred embodiment, the preparation process of the carbon electrode layer 50 includes: preparing a carbon-containing material slurry; applying the carbon-containing material slurry with a scraper, and obtaining the carbon electrode layer 50 after curing, and the carbon electrode layer 50 includes a main layer part and an electrode part.

[0034] In a preferred embodiment, the carbonaceous material slurry includes 2 to 5 parts of carbon material, 2 to 5 parts of resin binder, 3 to 8 parts of solvent and 1 to 3 parts of filler by weight. Preferably, the carbon material includes but is not limited to one or more of graphite, carbon black and graphene; the resin binder includes but is not limited to one or more of ethyl cellulose, polyvinyl pyrrolidone and sodium carboxymethyl starch; the filler includes but is not limited to one or more of nano-alumina, nano-zirconium oxide and nano-silicon oxide.

[0035] In a preferred embodiment, the average particle size of the filler is 3-10 nm. The average particle size of the filler includes but is not limited to the above range, which is beneficial to improving the strength of the carbon electrode layer 50 and facilitating the electron blocking effect of the filler.

[0036] In order to improve the coverage, uniformity and conductivity of the carbon electrode, preferably, the coating amount of the carbon-containing material slurry is 1 to 10 mg / cm 2 .

[0037] In a preferred embodiment, the thickness of the carbon electrode layer 50 is 5 to 20 μm. The thickness of the carbon electrode layer 50 includes but is not limited to the above range, and limiting it within the above range is conducive to improving the processability of the laminated structure, and is conducive to inhibiting the laminated structure from being damaged when subjected to applied pressure, thereby facilitating improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell.

[0038] In a preferred embodiment, the perovskite active layer 40 is prepared by a two-step anti-solvent spin coating method. Compared with other methods, the two-step anti-solvent spin coating method is conducive to forming a perovskite active layer 40 with more uniform components in each part, and is also conducive to improving the stability of the perovskite active layer 40, and the process is easy to operate.

[0039] In a preferred embodiment, the preparation process of the perovskite active layer 40 includes: preparing a perovskite precursor solution; spin coating the perovskite precursor solution on the surface of the mesoporous layer 30, dripping an anti-solvent, and obtaining a laminated structure containing the perovskite active layer 40 after annealing, wherein the spin coating process includes low-speed spin coating and high-speed spin coating, and the rotation speed of the low-speed spin coating is 460 to 1000 rpm, the time is 8 to 10 s, and the rotation speed of the high-speed spin coating is 4500 to 5200 rpm, and the time is 17 to 22 s. Preferably, the anti-solvent includes but is not limited to one or more of the group consisting of isopropyl ether, ethyl ether, ethyl acetate and diethyl carbonate.

[0040] In a preferred embodiment, the thickness of the perovskite active layer 40 is 400-560 nm. The thickness of the perovskite active layer 40 includes but is not limited to the above range, and limiting it within the above range is conducive to improving the absorption efficiency of photons, accelerating the separation and transmission of carriers, and thus helping to improve the photoelectric conversion efficiency of carbon-based perovskite solar cells.

[0041] In a preferred embodiment, the material of the perovskite active layer 40 is Cs 1-x FA x PbI3, wherein FA is formamidine, 0.77≤x≤0.82. The material of the perovskite active layer 40 includes but is not limited to the above range, and limiting it within the above range is conducive to having a more suitable band gap, better theoretical photovoltaic properties and longer carrier lifetime, thereby facilitating improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell.

[0042] In a preferred embodiment, when the material of the perovskite active layer 40 is Cs 0.21 FA 0.79 When the material of the perovskite active layer 40 is Cs, the pressure is 55-60 Pa, the heating rate in the heating stage is 8-10 ° C / min, the temperature in the insulation stage is 58-62 ° C, and the insulation time is 8-12 min; when the material of the perovskite active layer 40 is Cs 0.23 FA 0.77 When the material of the perovskite active layer 40 is Cs, the pressure is 20-55 Pa, the heating rate in the heating stage is 6-9 ° C / min, the temperature in the insulation stage is 40-50 ° C, and the insulation time is 4-8 min; when the material of the perovskite active layer 40 is Cs 0.19 FA 0.81When PbI3, the pressure is 65-100Pa, the heating rate in the heating stage is 7-9°C / min, the temperature in the insulation stage is 46-60°C, and the insulation time is 2-5min. For different types of perovskite active layers 40, the use of the above-mentioned preferred range of pressure, heating rate in the heating stage, temperature and insulation time in the insulation stage is beneficial to further improve the binding force between the perovskite active layer 40 and the carbon electrode layer 50, and to further improve the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, thereby further improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and at the same time, it is beneficial to further reduce the hysteresis effect.

[0043] In a preferred embodiment, when the thickness of the carbon electrode layer 50 is 5 to 10 μm, the pressure is 50 to 75 Pa, the heating rate in the heating stage is 6 to 7 ° C / min, the temperature in the insulation stage is 54 to 62 ° C, and the insulation time is 8 to 12 min; when the thickness of the carbon electrode layer 50 is 13 to 20 μm, the pressure is 30 to 58 Pa, the heating rate in the heating stage is 6 to 9 ° C / min, the temperature in the insulation stage is 47 to 60 ° C, and the insulation time is 7 to 11 min. For carbon electrode layers 50 of different thicknesses, the use of the above-mentioned preferred range of pressure, temperature in the insulation stage and insulation time is beneficial to further improve the binding force between the perovskite active layer 40 and the carbon electrode layer 50, and to further improve the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, thereby further improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and at the same time, it is beneficial to further reduce the hysteresis effect.

[0044] In a preferred embodiment, the electron transport layer 20 is prepared by chemical bath deposition, spin coating or magnetron sputtering. Compared with other methods, the above method is conducive to improving the interface contact between the electron transport layer 20 and the transparent conductive substrate 10, thereby accelerating the extraction and transmission of electrons and improving the photoelectric conversion efficiency of carbon-based perovskite solar cells.

[0045] In order to further improve the interface contact between the electron transport layer 20 and the transparent conductive substrate 10, thereby facilitating improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell, preferably, the thickness of the electron transport layer 20 is 20 to 60 nm; the material of the electron transport layer 20 includes but is not limited to one or more of the group consisting of titanium dioxide, tin dioxide and zinc oxide.

[0046] In a preferred embodiment, the mesoporous layer 30 is prepared by spin coating. Compared with other methods, the above method for preparing the mesoporous layer 30 is conducive to the orderly growth of the subsequent perovskite active layer 40 and improves the quality of film formation, thereby improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell.

[0047] In order to further improve the carrier transmission efficiency and further improve the photoelectric conversion efficiency of carbon-based perovskite solar cells, preferably, the thickness of the mesoporous layer 30 is 50 to 94 nm; the material of the mesoporous layer 30 includes but is not limited to one or more of the group consisting of titanium dioxide, aluminum oxide and zirconium oxide.

[0048] In a preferred embodiment, the transparent conductive substrate 10 includes but is not limited to one or more of the group consisting of FTO conductive glass, ITO conductive glass and IZO conductive glass. The above-mentioned transparent conductive substrate 10 has high light transmittance and good conductivity, and is suitable for preparing carbon-based perovskite solar cells.

[0049] The second aspect of the present application also provides a carbon-based perovskite solar cell, which is prepared by the preparation method of the carbon-based perovskite solar cell provided by the present application. The carbon-based perovskite solar cell prepared by the present application has the advantages of high photoelectric conversion efficiency and good stability.

[0050] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0051] Example 1

[0052] A method for preparing a carbon-based perovskite solar cell, comprising:

[0053] (1) Prepare FTO conductive glass with a square resistance of 15Ω / sq, and use laser to etch a rectangular insulating area on the conductive surface of the FTO conductive glass to prepare for the subsequent scraping of the carbon electrode layer 50; the remaining functional layers are all carried out on the unetched area of ​​the FTO conductive glass; ultrasonically clean the etched FTO conductive glass with deionized water, isopropanol, and ethanol for 25 minutes in turn, and then blow dry with an air gun for standby use;

[0054] (2) Preparation of titanium dioxide electron transport layer 20: Prepare a titanium tetrachloride aqueous solution with a concentration of 180 mmol / L; affix a polyimide tape to the other side of the insulating region of the FTO conductive glass, immerse the FTO conductive glass with the tape in the titanium tetrachloride aqueous solution, heat at 80° C. for 60 min, and then wash with deionized water until the surface of the FTO conductive glass is obviously unchanged; then heat on a heating plate at 120° C. for 10 min, and cool to room temperature;

[0055] (3) Preparation of titanium dioxide mesoporous layer 30: Commercial titanium dioxide (Dyesol, 30NR-D) and ethanol were mixed at a weight ratio of 1:5.9 and stirred for 16 hours to obtain titanium dioxide slurry; the titanium dioxide slurry was spin-coated on the surface of the titanium dioxide electron transport layer 20 at a speed of 4000 rpm for 20 seconds; then the slurry was transferred to a muffle furnace, kept at 520° C. for 30 minutes, and cooled;

[0056] (4) Cs 0.21 FA 0.79 Preparation of PbI3 perovskite active layer 40: 51 mg CsI, 137 mg FAI (formamidine iodide) and 462 mg PbI2 were weighed respectively, 145 mL DMSO and 489 μL DMF were transferred by a pipette, mixed and shaken for 1 hour, and filtered through a 0.22 μm polytetrafluoroethylene filter to obtain a perovskite precursor solution; the perovskite precursor solution was used as a spin coating solution, and a two-step anti-solvent spin coating method was adopted, first rotating at a low speed for 10 seconds, with a rotation speed of 1000 rpm, and then rotating at a high speed for 20 seconds, with a rotation speed of 4500 rpm. When the high-speed rotation reached the 10th second, 150 μL of isopropyl ether was added dropwise, and the mixture was transferred to a glove box and annealed at 165°C for 26 minutes;

[0057] (5) Preparation of the carbon electrode layer 50: Prepare a carbon-containing material slurry, wherein, by weight, the carbon-containing material slurry includes 1.2 parts of graphite, 1.4 parts of carbon black, 0.4 parts of graphene, 1.6 parts of ethyl cellulose, 0.4 parts of sodium carboxymethyl starch, 2.5 parts of terpineol, 0.3 parts of chlorobenzene, 0.2 parts of anisole and 1 part of nano-alumina (average particle size of 2 to 8 nm), and the solid content of the carbon-containing material slurry is 66.7%; in Cs 0.21 FA 0.79 The surface of the PbI3 perovskite active layer 40 is coated with the above-mentioned carbon-containing material slurry, and the coating amount of the carbon-containing material slurry is 6 mg / cm 2 After curing at 120°C for 20 min, the following laminated structure was obtained: FTO conductive glass / titanium dioxide electron transport layer / titanium dioxide mesoporous layer / Cs 0.21 FA 0.79 PbI3 perovskite active layer / carbon electrode layer 50, such as Figure 1 As shown, the carbon electrode layer 50 includes a main layer portion and an electrode portion, the main layer portion is arranged on a surface of the perovskite active layer 40 away from the transparent conductive substrate 10, the electrode portion is arranged on the transparent conductive substrate 10, and is arranged in contact with the electron transport layer 20, the mesoporous layer 30, and the perovskite active layer 40, and the electrode portion and the main layer portion are flush with each other on a surface of the side away from the transparent conductive substrate 10;

[0058] (6) applying a pressure of 60 Pa to the structure obtained in step (5) using a Hoffman clamp; transferring the Hoffman clamp containing the laminated structure to a muffle furnace, heating the mixture to 60° C. at a rate of 8° C. / min, keeping the temperature for 10 min, and then naturally cooling the mixture to room temperature in air to obtain a carbon-based perovskite solar cell.

[0059] In the carbon-based perovskite solar cell prepared in this embodiment, the thickness of the titanium dioxide electron transport layer 20 is 26 nm, the thickness of the titanium dioxide mesoporous layer 30 is 65 nm, and the Cs 0.21 FA 0.79 The thickness of the PbI3 perovskite active layer 40 is 462 nm, and the thickness of the carbon electrode layer 50 is 7 μm.

[0060] Example 2

[0061] The difference from Example 1 is that in step (6), the applied pressure is 10 Pa, the heating rate in the heating stage is 6° C. / min, the temperature in the insulation stage is 65° C., and the time is 2 min. The remaining steps are the same as in Example 1.

[0062] Example 3

[0063] The difference from Example 1 is that in step (6), the applied pressure is 100 Pa, the heating rate in the heating stage is 10° C. / min, the temperature in the insulation stage is 40° C., and the time is 12 min. The remaining steps are the same as in Example 1.

[0064] Example 4

[0065] The difference from Example 1 is that in step (6), the applied pressure is 150 Pa, the heating rate in the heating stage is 15° C. / min, the temperature in the insulation stage is 70° C., and the time is 15 min. The remaining steps are the same as in Example 1.

[0066] Example 5

[0067] The difference from Example 1 is that the coating amount of the carbon-containing material slurry is changed so that the thickness of the carbon electrode layer 50 is 5 μm; in step (6), the applied pressure is 75 Pa, the heating rate in the heating stage is 6° C. / min, the temperature in the insulation stage is 54° C., and the time is 8 min. The remaining steps are the same as in Example 1.

[0068] Example 6

[0069] The difference from Example 1 is that the coating amount of the carbon-containing material slurry is changed so that the thickness of the carbon electrode layer 50 is 20 μm; in step (6), the applied pressure is 30 Pa, the heating rate in the heating stage is 9° C. / min, the temperature in the insulation stage is 60° C., and the time is 11 min. The remaining steps are the same as in Example 1.

[0070] Example 7

[0071] The difference from Example 1 is that in step (6), the applied pressure is 55 Pa, the heating rate in the heating stage is 10° C. / min, the temperature in the insulation stage is 58° C., and the time is 12 min. The remaining steps are the same as in Example 1.

[0072] Example 8

[0073] The difference from Example 1 is that in step (6), the applied pressure is 60 Pa, the heating rate in the heating stage is 8° C. / min, the temperature in the insulation stage is 62° C., and the time is 8 min. The remaining steps are the same as in Example 1.

[0074] Example 9

[0075] The difference from Example 1 is that in step (6), the perovskite precursor solution is prepared so that the material of the prepared perovskite active layer 40 is Cs 0.23 FA 0.77 PbI3; the applied pressure is 20Pa, the heating rate in the heating stage is 9°C / min, the temperature in the insulation stage is 40°C, and the time is 8min; the remaining steps are the same as in Example 1.

[0076] Example 10

[0077] The difference from Example 1 is that in step (6), the perovskite precursor solution is prepared so that the material of the prepared perovskite active layer 40 is Cs 0.23 FA 0.77 PbI3; the applied pressure is 55Pa, the heating rate in the heating stage is 6°C / min, the temperature in the insulation stage is 50°C, and the time is 4min; the remaining steps are the same as in Example 1.

[0078] Embodiment 11

[0079] The difference from Example 1 is that in step (6), the perovskite precursor solution is prepared so that the material of the prepared perovskite active layer 40 is Cs 0.19 FA 0.81 PbI3; the applied pressure is 65Pa, the heating rate in the heating stage is 9°C / min, the temperature in the insulation stage is 46°C, and the time is 5min; the remaining steps are the same as in Example 1.

[0080] Example 12

[0081] The difference from Example 1 is that in step (6), the perovskite precursor solution is prepared so that the material of the prepared perovskite active layer 40 is Cs 0.19 FA 0.81PbI3; the applied pressure is 100Pa, the heating rate in the heating stage is 7°C / min, the temperature in the insulation stage is 60°C, and the time is 2min; the remaining steps are the same as in Example 1.

[0082] Comparative Example 1

[0083] The difference from Example 1 is that the treatment process of step (6) is not performed. The remaining steps are the same as those of Example 1.

[0084] The light source is Newport Oriel Sol 3A from the United States, at 100mW·cm -2 The short-circuit current density J of the carbon-based perovskite solar cells prepared in all the above embodiments and comparative examples of the present application was tested under illumination conditions. sc , open circuit voltage V oc , fill factor FF and photoelectric conversion efficiency PCE, where the test area of ​​carbon-based perovskite solar cells is 0.1cm 2 , the test results are shown in Table 1. Figure 2 and Figure 3 The forward scanning and reverse scanning JV curves of the carbon-based perovskite solar cells prepared in Example 1 of the present application and Comparative Example 1 are shown respectively.

[0085] Table 1

[0086]

[0087] The residual stress of the perovskite active layer 40 in all the above embodiments and comparative examples of the present application was calculated by the Hall-Williams formula, and the calculation results are shown in Table 2. According to the Mott-Gurney law, the defect state density of the perovskite active layer 40 and the hole mobility of the carbon-based perovskite solar cell in all the above embodiments and comparative examples of the present application were calculated, and the calculation results are shown in Table 2.

[0088] Table 2

[0089]

[0090]

[0091] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0092] Comparing Example 1 with Comparative Example 1, it can be seen that the present invention Figure 1The stacked structure shown is subjected to in-situ pressure annealing, which can cause the perovskite active layer 40 to undergo secondary crystallization, thereby reducing the defect state density of the perovskite active layer 40, effectively reducing the stress inside the perovskite active layer 40 itself and between it and the carbon electrode layer 50, improving the binding force between the perovskite active layer 40 and the carbon electrode layer 50, improving the interface contact between the two, improving the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, improving the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and reducing the hysteresis effect. Moreover, the improvement of the interface contact between the perovskite active layer 40 and the carbon electrode layer 50 can effectively inhibit the infiltration of external moisture, thereby improving the stability of the carbon-based perovskite solar cell.

[0093] By comparing Examples 1 to 4, it can be seen that the applied pressure, the heating rate in the heating stage, the temperature and time in the insulation stage include but are not limited to the preferred range of the present application. Limiting them within the preferred range of the present application is beneficial to improving the binding force between the perovskite active layer 40 and the carbon electrode layer 50, and is beneficial to improving the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, thereby helping to improve the photoelectric conversion efficiency of carbon-based perovskite solar cells, and at the same time helping to reduce the hysteresis effect.

[0094] By comparing Examples 1, 5 and 6, it can be seen that adopting the pressure within the above preferred range, the heating rate in the heating stage, the temperature and time in the insulation stage is beneficial to further improve the binding force between the perovskite active layer 40 and the carbon electrode layer 50, and is beneficial to further improve the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, thereby helping to further improve the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and at the same time is beneficial to further reduce the hysteresis effect.

[0095] By comparing Examples 1, 7 and 8, Examples 1, 9 and 10, and Examples 1, 11 and 12 respectively, it can be seen that for different types of perovskite active materials, adopting the pressure in the above preferred range, the heating rate in the heating stage, the temperature and time in the insulation stage is beneficial to further improve the binding force between the perovskite active layer 40 and the carbon electrode layer 50, and is beneficial to further improve the extraction and transmission of hole carriers between the perovskite active layer 40 and the carbon electrode layer 50, thereby helping to further improve the photoelectric conversion efficiency of the carbon-based perovskite solar cell, and at the same time helping to further reduce the hysteresis effect.

[0096] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-based perovskite solar cell, comprising the step of preparing a laminated structure, wherein the laminated structure comprises a transparent conductive substrate (10) and an electron transport layer (20), a mesoporous layer (30), a perovskite active layer (40) and a carbon electrode layer (50) sequentially stacked on the surface thereof, characterized in that: After the step of preparing the laminated structure, the preparation method comprises: A pressure perpendicular to the stacked structure is applied to the stacked structure while performing an annealing treatment to obtain the carbon-based perovskite solar cell.

2. The method for preparing a carbon-based perovskite solar cell according to claim 1, characterized in that: The pressure is applied to the laminate structure by using a Hoffman clamp; and / or, the annealing treatment includes a heating stage, a heat preservation stage and a cooling stage; Preferably, the pressure is 10-100 Pa, the heating rate in the heating stage is 6-10° C. / min, the temperature in the insulation stage is 40-65° C., and the insulation time is 2-12 min.

3. The method for preparing a carbon-based perovskite solar cell according to claim 1, characterized in that: The carbon electrode layer (50) is prepared by a scraping method; Preferably, the carbon electrode layer (50) has a thickness of 5 to 20 μm.

4. The method for preparing a carbon-based perovskite solar cell according to claim 2, characterized in that: The perovskite active layer (40) is prepared by a two-step anti-solvent method and spin coating method; Preferably, the thickness of the perovskite active layer (40) is 400-560 nm; and / or the material of the perovskite active layer (40) is Cs 1-x FA x PbI3, where FA is formamidine, 0.77≤x≤0.

82.

5. The method for preparing a carbon-based perovskite solar cell according to claim 4, characterized in that: When the material of the perovskite active layer (40) is Cs 0.21 FA 0.79 When PbI3, the pressure is 55-60Pa, the heating rate in the heating stage is 8-10°C / min, the temperature in the insulation stage is 58-62°C, and the insulation time is 8-12min; When the material of the perovskite active layer (40) is Cs 0.23 FA 0.77 When PbI3, the pressure is 20-55 Pa, the heating rate in the heating stage is 6-9°C / min, the temperature in the insulation stage is 40-50°C, and the insulation time is 4-8 min; When the material of the perovskite active layer (40) is Cs 0.19 FA 0.81 When PbI3, the pressure is 65-100 Pa, the heating rate in the heating stage is 7-9°C / min, the temperature in the insulation stage is 46-60°C, and the insulation time is 2-5 min.

6. The method for preparing a carbon-based perovskite solar cell according to claim 5, characterized in that: When the thickness of the carbon electrode layer (50) is 5 to 10 μm, the pressure is 50 to 75 Pa, the heating rate in the heating stage is 6 to 7° C. / min, the temperature in the insulation stage is 54 to 62° C., and the insulation time is 8 to 12 min; When the thickness of the carbon electrode layer (50) is 13-20 μm, the pressure is 30-58 Pa, the heating rate in the heating stage is 6-9° C. / min, the temperature in the insulation stage is 47-60° C., and the insulation time is 7-11 min.

7. The method for preparing a carbon-based perovskite solar cell according to claim 4, characterized in that: The electron transport layer (20) is prepared by chemical bath deposition, spin coating or magnetron sputtering; Preferably, the thickness of the electron transport layer (20) is 20-60 nm; and / or the material of the electron transport layer (20) is selected from one or more of the group consisting of titanium dioxide, tin dioxide and zinc oxide.

8. The method for preparing a carbon-based perovskite solar cell according to claim 4, characterized in that: The mesoporous layer (30) is prepared by spin coating; Preferably, the thickness of the mesoporous layer (30) is 50-94 nm; and / or the material of the mesoporous layer (30) is selected from one or more of the group consisting of titanium dioxide, aluminum oxide and zirconium oxide.

9. The method for preparing a carbon-based perovskite solar cell according to claim 4, characterized in that: The transparent conductive substrate (10) is one or more selected from the group consisting of FTO conductive glass, ITO conductive glass and IZO conductive glass.

10. A carbon-based perovskite solar cell, characterized in that: The carbon-based perovskite solar cell is prepared by the preparation method of the carbon-based perovskite solar cell according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • method of production of new racemic or optically active derivatives of (piperidyl-2)-phenylmethanol

    CS100077B1

  • Perovskite solar cell and preparation method thereof

    CN112201755A

  • PEG-modified carbon electrode and preparation method thereof and perovskite battery prepared from PEG-modified carbon electrode

    CN112614942A

  • Preparation method of perovskite solar cell

    CN115172610A

Cited By

  • Perovskite photoelectric conversion element and method for manufacturing a perovskite photoelectric conversion element

    JP2026146490A

  • Perovskite photoelectric conversion element and method for manufacturing perovskite photoelectric conversion element

    WO2026186582A1